Veering off track in U.S. high schools? Redirecting student trajectories by disrupting punishment and math course-taking tracks. (February 2020) - Jabbari, Jason; Johnson, Odis
Highlights: Not taking Algebra (or higher) in 9th grade is associated with increased odds of being suspended in 11th grade—when accounting for prior suspensions. Being suspended in 11th grade is associated with decreased odds of taking Pre-Calculus (or higher) in 12th grade—when accounting for prior math course-taking. Both suspensions and advanced math courses can significantly influence dropout status and college attendance. Disadvantages appear to accumulate when students are excluded both from advanced math course-taking and through suspensions. Students in punishment "tracks" can be redirected towards college through math opportunities. Abstract: Students in punishment "tracks" are rarely in advanced course-taking "tracks" in high school. Yet, there is little research that demonstrates the relationships between punishment and advanced course-taking, nor research that demonstrates how punishment and advanced course-taking together can impact long-term student trajectories. Using multi-level modeling with a national longitudinal study of high school students, we observed reciprocal disruptions. Advanced math courses significantly impacted future suspensions when accounting for prior suspensions, while suspensions significantly impacted future advanced math course-taking when accounting for prior math courses. We also observed that both suspensions and advanced math courses significantly influenced dropout status and college attendance. As baseline measures often maintained a strong relationship with their respective outcomes, disadvantages appeared to accumulate when students were excluded both from advanced math courses and through suspensions. Nevertheless, while we cannot undo the harms of previous disadvantages in punishment, our findings suggest that we can facilitate potential turning points in students' lives by opening up new opportunities in math. By doing so, we can redirect students towards college. We conclude with a discussion of implications for policy and practice.